2008 Winter Simulation Conference 2008
DOI: 10.1109/wsc.2008.4736282
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation with Design For Six Sigma in a server manufacturing environment

Abstract: This research presents an integrated simulation modeling-Design For Six Sigma (DFSS) framework to study the design and process issues in a server manufacturing environment. The server assembly process is characterized by long cycle times, high fall-out rates and extremely complex assembly operations. To ensure on-time customer delivery, these enterprises adopt a make-to-plan and build-to-order philosophy. However, this model is extremely complex, resulting in wastes and inefficiencies in the associated process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The first three stages are greatly connected with the customer requirements (Seifert, 2005) or product characteristics that are critical-toquality (CTQ). At the Define stage the problem is stated, sponsors are identified, the scopes of the project are settled and the metrics are chosen (Ramakrishnan & Tsai & Drayer, & Srihari, 2008). The measure stage is associated with the measurement of factors influencing the CTQ product with the usage of statistical tools.…”
Section: Six Sigmamentioning
confidence: 99%
See 2 more Smart Citations
“…The first three stages are greatly connected with the customer requirements (Seifert, 2005) or product characteristics that are critical-toquality (CTQ). At the Define stage the problem is stated, sponsors are identified, the scopes of the project are settled and the metrics are chosen (Ramakrishnan & Tsai & Drayer, & Srihari, 2008). The measure stage is associated with the measurement of factors influencing the CTQ product with the usage of statistical tools.…”
Section: Six Sigmamentioning
confidence: 99%
“…DFSS is a method for radical changes and introduction of new processes. It usually deals with the defects at the early stages of production (Ramakrishnan & Tsai & Drayer, & Srihari, 2008). There are several methods accepted in DFSS that may vary depending on the company and/or company strategy: DMADV (Define, Measure, Analyze, Design, Verify), IDOV (Identify, Design, Optimize, Validate), DIDES (Define, Initiate, Design, Execute, Sustain), IIDOV (Invent, Innovate, Develop, Optimize, Verify), CDOV (Concept development, Design Development, Optimization, Verify, certification), DCOV (Define, Characterize, Optimize, Verify), IDEAS (Identify, Design, Evaluate, Assure, Scale-up) (Shahin, 2008).…”
Section: Six Sigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers discuss the integration of Six Sigma and computer simulation to improve outcomes, such as improving a patient's experience in hospital (e.g., . Ramakrishnan et al (2008) mention that approaches of LSS have been effective in term of improving performance by reducing waste in the design and operational processes. Aft (2001), suggested that "Lean Sigma is a customer focused, well defined, problem solving methodology supported by a handful of powerful statistical tools."…”
Section: Lean Six Sigma and Simulationmentioning
confidence: 99%
“…As suggested by Ramakrishnan et al (2008), simulation techniques are recommended within Six Sigma Methodology for: quantifying different performance metrics to make better decisions before the implementation phase; studying alternatives and perform ‘what-if’ analyses; identify interactions between sub-systems; provide data analysis to understand better the system’s nature; and accounting both structural and random variability. …”
Section: Introductionmentioning
confidence: 99%